Military operations and the EU's identity as an international security actor. Issue 4 (2nd October 2019) - Palm, Trineke; Crum, Ben
ABSTRACT: For long, its lack of military means served to single the European Union out as a "civilian" or "normative power". However, since 2003 twelve EU military operations have been launched. On the basis of a comprehensive analysis of all EU military mission so far, this article seeks to establish how these missions have evolved over time and how they have affected the character of the EU as an international actor. For this purpose, the article outlines four ideal-typical conceptions of the EU's international identity and operationalises them along two underlying dimensions: justification (the purpose of military operations) and policy-embeddedness (the coordination between military means and other foreign policy instruments). Analysing the military operations along these two axes, the article suggests that the EU has been evolving towards a "Liberal Power" identity, as is reflected in a shift from value-based to utility-based justifications, while military operations have at the same time become more embedded in the EU's overall foreign policies.